(untitled) (Research, Society and Development, 2020)
To investigate in the literature the behavior of different levels of selenium and the activity of glutathione peroxidase (GPx-Se) observed in patients with cystic fibrosis. This is an integrative literature review, carried out by searching for original articles, with no year limit, in English and Portuguese, indexed in the PubMed, Scopus and Web of Science databases. 56 articles were retrieved, of which 16.1% (n = 9) were included in this review, for reading the full text. It was observed that of the studies compiled, 33.3% (n=3) identified a reduction in the selenium concentrations, as well as in the GPx activity, although 11.1% (n=1) reported an increase only in the plasma concentrations of the mineral, and another 22.2% (n=2), added by GPx. On the other hand, 33.3% (n=3) of the studies did not find any significant differences regarding these parameters compared between the control group and the group with cystic fibrosis. It is concluded that the levels of selenium and the activity of the enzyme Glutathione Peroxidase Dependent on Selenium (GPx-Se) can present different behaviors in conditions of Cystic Fibrosis (CF), however, the fragile reasoning, which justify controversial and little results consistent, reinforces the need for further studies to deepen the theme.